A Case of Pyridoxine Dependent Epilepsy Presented with Status Epilepticus - Senem Ayça; Hamide Betül Gerik Çelebi; Sırrı Çam; Muzaffer Polat (Journal of Pediatric Emergency and Intensive Care Medicine, 2019)

(untitled)
Pyridoxine-dependent epilepsy (PDE) is a rare autosomal recessive encephalopathy due to mutations in the ALDH7A1 gene. Intractable seizures are the most frequent clinical form in the early infantile period. A case of a 4-month-old female patient presented to our hospital with status epilepticus. Her seizures started in the neonatal period and partial response to phenobarbital was seen. Her seizures could not be controlled with appropriate antiepileptic treatment. The seizure stopped with 100 mg of intravenous pyridoxine administration. The diagnosis of PDE was considered and ALDH7A1 gene mutation analysis revealed homozygous missense mutation. Pyridoxine should be administrated in case of intractable seizures and should be included in status epilepticus treatment protocol. Diagnosis of PDE should be considered especially in our country where consanguineous marriage is frequently seen.